(untitled) (Biological Sciences - PJSIR, 1995)
Different fish samples: sardine, macaroni, bourri, bolti and shark were used for the preparation of fish sauce. The applied proteolytic enzymes were: papain, trypsin, ficin and bromelain. Ripening periods were extended for 180 days at 37°. Changes in pH values, total soluble nitrogen (TSN), amino nitrogen (AN), volatile basic nitrogen (VBN), volatile organic acids (VOA) and in the free amino acid during fermentation period were considered in sardine; while the other fish samples were analyzed only before and by the end of fermentation period. The statistial analyses were used for comparing between the obtained results. the available data assured in the production of fish sauce rather than the other investigated enzymes. Such conclusion was based on regression analysis from which the added enzymes could be ascendingly ordered with respect to amino nitrogen of sardine sauce as follows: papain, R2=0.725; trypsin, R2= 0.7629; bromelain, R2=0.8219 and ficin, R2=0.8975.